Moral Networks: A Sociological Study on Illicit Self-Cultivation of Cannabis for Psychoactive use in Brazil - Castro, Marco; Fraga, Paulo (International Journal of Criminology and Sociology, 2023)
The use of psychoactive drugs is a social practice commonly observed in all societies. This article aims to present the moral grammar of actors who grow marijuana for their own use in Brazil. This study employed a qualitative methodology based on direct observation and semi-structured interviews. Regarding research ethics, all institutional principles were considered, like obtaining informed consent and guaranteeing the privacy of participants and the confidentiality of information. We found that these actors establish a sui generis morality through their practices. From this perspective, it can be conjectured that this network of actors who grow their own marijuana configures a specific moral grammar through the language devices they mobilize in response to the judgments, criticisms and moral accusations they face, whether formal or informal. Moreover, through the interviews, it was possible to verify how the relations of mutual assistance in this moral network of actors who grow their own marijuana are shaped by the actions, interactions, associations and moral aggregations among them. In this way, the relations of reciprocity and cooperation among these moral actors configure a kind of solidarity specific to this network. Therefore, the home cultivation of marijuana is analyzed as a legitimate moral feeling of liberation in relation to the formal and informal repressions faced by these actors.